2020
DOI: 10.1016/j.ygyno.2020.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term survival of total abdominal radical hysterectomy and laparoscopy-assisted radical vaginal hysterectomy in patients with early cervical cancer: Korean multicenter, retrospective analysis

Abstract: Comparison of long-term survival between total TARH and LARVH was investigated in patients with early cervical cancer. • The 5-year PFS and OS rates did not differ statistically between TARH and LARVH. • The non-inferiority of LARVH to TARH in 5-year PFS and OS rates was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
(38 reference statements)
2
10
0
Order By: Relevance
“…These two studies compared the recurrence and survival results of patients with early cervical cancer undergoing open surgery and minimally invasive surgery, and found that the survival of patients in the open surgery group was significantly better than that of the minimally invasive surgery group, which completely contrary to previous results ( 10 16 ). The same results were obtained in subsequent studies by other institutions ( 17 , 18 ). It caused great shock and controversy in the international community.…”
Section: Discussionsupporting
confidence: 89%
“…These two studies compared the recurrence and survival results of patients with early cervical cancer undergoing open surgery and minimally invasive surgery, and found that the survival of patients in the open surgery group was significantly better than that of the minimally invasive surgery group, which completely contrary to previous results ( 10 16 ). The same results were obtained in subsequent studies by other institutions ( 17 , 18 ). It caused great shock and controversy in the international community.…”
Section: Discussionsupporting
confidence: 89%
“…These two studies compared the recurrence and survival results of patients with early cervical cancer undergoing open surgery and minimally invasive surgery, and found that the survival of patients in the open surgery group was signi cantly better than that of the minimally invasive surgery group, which completely contrary to previous results [8][9][10][11][12][13][14][15] . The same results were obtained in subsequent studies by other institutions 16,17 . It caused great shock and controversy in the international community.…”
Section: Toxicities Of Postoperative Radiotherapysupporting
confidence: 88%
“…Except for Li [16], Park [17] and Kwon [26], all the other studies avoided the use of uterine manipulators. Moreover, Kanno [14], and Fugesi [24] explixity declared that they systematically removed surgical specimens into a collection bag.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Köhler et al [15] proposed the largest series with 389 patients undergone to LARVH and the longest mean FUP of 99 months (3 years DFS 96.8%; 3 years OS 98.5%; 4.5 years DFS 95.7%; 4.5 years DFS 97.6%). Kwon et al [26], vice versa, reported the largest comparative study, with the arm of LARVH composed of 252 patients, which presented a 5 years DFS and OS of 86.6% and 88% during a mean of 82 months FUP. Li et al [16] is the latest article published, with 137 patients and 53 months of FUP, showing a 5 years DFS of 96.4% and 5 years OS of 96.8%.…”
Section: Oncological Outcomesmentioning
confidence: 99%